Narrating Care and Its Silences: Gendered Care and Familial Responsibility in How to Make Millions Before Grandma Dies - Jaisuekun, Kwanchanok (Multidisciplinary Digital Procedia, 2026)
This study analyzes how the Thai film How to Make Millions Before Grandma Dies employs narrative to reshape socio-historical understandings of aging and gender in contemporary Thailand. In a rapidly aging society with limited formal welfare infrastructure, eldercare remains predominantly privatised within the family. Rather than addressing this condition through policy discourse, the film makes it comprehensible through intimate, intergenerational storytelling. Through close narrative analysis of the film, this article examines how gendered responsibility is symbolically reorganised without being structurally redistributed. The narrative centres on a young man who becomes the primary caregiver to his grandmother, seemingly disrupting conventional gender expectations that associate caregiving with femininity. His transformation, from inheritance-seeking opportunist to emotionally committed grandson, invites viewers to reimagine masculinity as capable of tenderness and responsibility. However, this apparent reconfiguration does not entail a structural redistribution of care. Alongside his visible moral growth persists the quieter but indispensable labour of his mother, whose caregiving, marked by economic sacrifice, exhaustion, and filial obligation, remains narratively understated. Drawing on feminist care theory, moral economy, and masculinity, this study argues that the film performs a double movement: it renders male caregiving exceptional and transformative while normalising women’s care work as ordinary and expected. In doing so, the narrative reshapes the moral imagination of responsibility without destabilising the familial regime that confines eldercare within kinship structures. By reading the film as a cultural site in which aging, gender, and obligation are negotiated, the article demonstrates how storytelling both reveals and obscures the sociohistorical conditions of care in late-modern Thailand. The film thus illuminates not only the emotional transformation of a grandson but also the enduring structural centrality of maternal labour.